Apakah Kinerja Lingkungan Memoderasi Pengaruh Biaya Lingkungan Terhadap Pengungkapan Informasi Lingkungan? - Baniady Gennody Pronosokodewo; Zidni Husnia Fachrunisa; Rahandhika Ivan Adyaksana (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2022)
Companies with environmental costs that are efficient and have good environmental performance can provide trade-offs on a sustainable supply chain that have a positive impact on the environmental information disclosure. This study examines the extent to which environmental performance moderate environmental costs in explaining the disclosure of general environmental information. This research was conducted to determine the role of environmental performance in moderating the effect of environmental costs allocated by the company on the environmental information disclosure. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) since 2015-2019. Data processing for testing research hypotheses was carried out using WarpPLS software. The result of this research is that environmental costs have a positive effect on the environmental information disclosure. Companies that allocate environmental costs will disclose environmental information as a form of realization of the costs that have been incurred. Environmental information disclosure can also be used as a benchmark for the successful implementation of activities carried out by the company in an effort to prevent and overcome environmental damage. However, environmental performance does not moderate the effect of environmental costs on the environmental information disclosure. Environmental performance measurement in PROPER has not paid attention to aspects of environmental costs incurred and environmental information disclosure.